2019
DOI: 10.1101/653964
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Reliability of Chronically Implanted Thin-Film Electrodes in Human Arm Nerves for Neuroprosthetic Applications

Abstract: Direct stimulation of peripheral nerves can successfully provide sensory feedback to amputees while using hand prostheses. Recent clinical studies have addressed this important limitation of current prostheses solutions using different implantable electrode concepts. Longevity of the electrodes is key to success. We have improved the long-term stability of the polyimide-based transverse intrafascicular multichannel electrode (TIME) that showed promising performance in clinical trials by integration of silicon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Details concerning design and fabrication can be found in Refs. [14,22]. S2 and S3 received also another TIME implant in the peroneal nerve.…”
Section: Intraneural Stimulation For Evoking Artificial Sensationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details concerning design and fabrication can be found in Refs. [14,22]. S2 and S3 received also another TIME implant in the peroneal nerve.…”
Section: Intraneural Stimulation For Evoking Artificial Sensationsmentioning
confidence: 99%
“…The potential resulted from the average of four pulses (the first one of a five-pulse train was removed) with a current amplitude of 20 μA and a pulse width of 300 μs, repeated at a frequency of 1 Hz. While a safety margin has been applied in functional assessment in the patients [8], this paper uses 150 kΩ as maximum impedance for the definition of electrically functional stimulation contact sites which corresponds to 3 V as the maximum output voltage swing of the stimulator [22] including a safety margin. Preimplant ultrasound image of the nerve of interest in S1 is shown.…”
Section: Intraneural Electrode Functionalitymentioning
confidence: 99%
See 1 more Smart Citation
“…There was no necrosis, the formation of fibrotic capsule was limited, and all the electrodes were stable [189]. More recent studies with transradial amputees have shown the feasibility of TIME implantation in the median and ulnar nerves for 6 months [104,177]. The electrodes used in this study were polyimide-based and had silicon carbide adhesion layers which contributed to their stability.…”
Section: Long-term Outcomesmentioning
confidence: 80%
“…This mapping procedure is mostly performed by an expert (e.g., clinician or bioengineer), and because it depends also by the number of ASs of the implanted electrode, it can have a long duration. For example, the implant of intraneural electrodes (e.g., TIME; Čvančara et al, 2019) requires four TIMEs for a total of 56 ASs available for the direct nerve stimulation (Petrini, Valle, Bumbasirevic, et al, 2019; Petrini, Valle, Strauss, et al, 2019). Each AS must be tested individually, and the stimulation parameters are unknown a priori.…”
Section: Electrical Neurostimulation As a Tool To Restore Touch Sensa...mentioning
confidence: 99%